New material of Seggeurius amourensis (Paenungulata, Hyracoidea), including a partial skull with intact basicranium. Issue 1 (2nd January 2016) - Benoit, Julien; Crochet, Jean-Yves; Mahboubi, Mohammed; Jaeger, Jean-Jacques; Bensalah, Mustapha; Adaci, Mohammed; Tabuce, Rodolphe
ABSTRACT: Seggeurius is the basal-most hyracoid known to date, and one of the earliest known fossil afrotherians. This taxon has a dramatic importance in mammalian phylogeny, but until now it was known from dental remains only. Here we describe previously unpublished material of Seggeurius, including some mandibular and maxillary fragments, and a braincase. This study is the first to thoroughly describe and discuss the morphology of the ear region and osseous inner ear of a Paleogene hyracoid. It allows a reappraisal of some important characters that are often used in cladistic analyses of Paenungulata. In particular, it seems that in stem hyracoids the orbit is located caudally, the eustachian sac is absent or reduced, the course of the internal carotid artery is intrabullar and medial, and a deep epitympanic sinus, a basisphenoid contribution to the bulla, and the stapedial artery are present. The cochlear canal is rather flattened, and the secondary common crus was rapidly lost. A cladistic analysis of stem placental mammals highlights three derived traits shared by Seggeurius and stem sirenians (the tuber-shaped postglenoid process, the squared and massive mastoid apophysis of the petrosal, and the presence of a swelling on the septum metacochleare) and supports molecular analysis that hypothesizes a Hyracoidea-Sirenia sister-group relationship. This study demonstrates how useful the petrosal and labyrinthine characters of fossils can be for mammalian phylogenetic inference. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Benoit, J., J.-Y. Crochet, M. Mahboubi, J.-J. Jaeger, M. Bensalah, M. Adaci, and R. Tabuce. 2015. New material of Seggeurius amourensis (Paenungulata, Hyracoidea), including a partial skull with intact basicranium. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2015.1034358.